(untitled) - Sanders, Roger E. (New York, 2002)
This authoritative reference offers complete coverage of all material on the three DB2 exams. You'll find exam objectives at the beginning of each chapter, helpful exam tips, end-of-chapter practice questions, and photographs and illustrations. The bonus CD-ROM contains practice tests, and hundreds of questions. This comprehensive guide will not only help you pass the certification exams, but will also serve as an invaluable on-the-job reference
Keywords: Database management; Computer programs